SEXUAL HARASSMENT IN ACADEMICS: THE PARADIGM OF LEGAL EVALUATION IN LITHUANIA - Jurka, Raimundas; Jurkienė, Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article focuses on the insights` analysis of the nowadays relevant social problems, related to sexual harassment in the academics, its legal evaluation in Lithuania. It is discussed, whether sexual harassment situations, that could be faced or happened in academics, could be seen as the ethic, moral violations or even more – criminal deeds. The authors go into deep and analyse the relationships between culprit and victim as they are not equal as such in the academic community. They have vertical relations, for instance, a lecturer and a student, etc. Then the principal question is raised – whether the guilty of the culprit should be proved / argued using presumption of innocence or there is a converse – the words and emotions of a victim take the prior place to incriminate a culprit. Another one question should be seen as the relevant one – does the legal situation change if there are enough assumptions to say “a culprit intended to have intimate relations with the victim”? It is also argued, that one of the biggest problems to uncover the situation’s real face is time of victim’s keeping silence as a victim, usually, is depending on culprit’s will (for instance, the lecturer and the student still have educational relations).